1992
DOI: 10.1177/028418519203300117
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Variability in the Radiographic Diagnosis of Adult Outpatient Pneumonia

Abstract: Acute chest radiographs were obtained from 319 adult patients with acute respiratory infections. Where a lower respiratory infec tion was diagnosed, follow-up chest radiographs were obtained in most patients. A radiologie panel diagnosed pneumonia in 21 pa tients. The agreements between the panel and 3 independent inter preters, 2 residents in radiology, and one senior chest physician, were assessed. Also the reports given by the specialist in radiology at the Department of Radiology were compared with the pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
13

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 7 publications
1
25
0
13
Order By: Relevance
“…20,23 Several of these studies have also estimated sensitivity, specificity and predictive values of chest X-rays for the diagnostic of pneumonia, its etiology and mortality. 5,6,15,16,19 When the above mentioned studies evaluated the interobserver agreement in order to define the presence of pneumonia in both children and adults, the results were poor to moderate (< 0.4 to 0.59), [3][4][5][6][11][12][13][14]24 while the percentage of agreement ranged between 41% and 87%. 18,[21][22][23]25 These values, however, depended on the specialty, expertise and level of training of readers, [3][4][5][6]11,14,16,18,19,21,24,25 and the radiological characteristics evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…20,23 Several of these studies have also estimated sensitivity, specificity and predictive values of chest X-rays for the diagnostic of pneumonia, its etiology and mortality. 5,6,15,16,19 When the above mentioned studies evaluated the interobserver agreement in order to define the presence of pneumonia in both children and adults, the results were poor to moderate (< 0.4 to 0.59), [3][4][5][6][11][12][13][14]24 while the percentage of agreement ranged between 41% and 87%. 18,[21][22][23]25 These values, however, depended on the specialty, expertise and level of training of readers, [3][4][5][6]11,14,16,18,19,21,24,25 and the radiological characteristics evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Single clinical signs as well as diagnostic rules consisting of a set of criteria do not provide satisfactory performances in predicting the presence of pneumonia [8±11]. Chest radiographs are also only of limited value in the imaging of mild infiltrates [12,13]. Moreover, since only every 10th or 20th patient with LRTI is expected to have true pneumonia [14], thus resulting in a low prevalence, the positive predictive value of any diagnostic rule will be low.…”
Section: Detecting Mild Pneumoniamentioning
confidence: 99%
“…Previous studies have shown great variation in the interpretation of the radiological diagnosis of various other diseases (9,13). CT has not been sufficiently evaluated as a method of diagnosing acute sinusitis, nor as to interobserver variation (5, 14,17).…”
mentioning
confidence: 99%